(untitled) (Bangladesh Journal of Pharmacology, 2018)
New series of pyrazoline spacer compounds were prepared by the reaction between benzimidazole chalcones and (2-methyl-5-nitro-imidazole-1-yl)-acetic acid hydrazide by the sensible use of Michael addition. The building blocks used for the synthesis of pyrazoline derivatives were opted by using virtual screening by molinspiration search engine. The hypothetically resulted pyrazoline spacer compounds from this list are checked for their reliability on other in silico drug designing online web services like PASS online bioactivity, Swiss ADME predictor. The docking study on final four pyrazoline compounds was carried out using Accelrys Discovery Studio 3.5. These synthesized compounds were, later, characterized with the help of UV, IR, mass and 1H NMR techniques. These compounds were further screened for their in vitro antimalarial effect. The PASS, Swiss ADME assisted docking approach and the use of combo heterocyclic ring with pyrazoline scaffold were found to be beneficial to derive and synthesize effective antimalarial agents in the present study. Video Clip of Methodology: 6 min 20 sec: Click to watch